(DE)SECURITIZING COLLECTIVES OF THE BRAZILIAN CERRADO AND THE IMPLEMENTATION OF AN AGRIBUSINESS COMPLEX/Coletivos (de)securitizantes do Cerrado Brasileiro e a implementação de um complexo do agronegócio - Pfrimer, Matheus Hoffmann; Barbosa Júnior, Ricardo César (REVISTA NERA, 2016)
The Cerrado biome has been intentionally unregulated. For this reason we understand it as a space of (in)security, this has allowed for the implementation of an agribusiness complex that has resulted in the rapid expansion of the agricultural frontier at the cost of devastating its native landscape. Yet, the academic literature is lacking in a geopolitical appraisal of the biome. In this paper, we discuss the actor-networks present within the securitizing/desecuritizing dispute for space in the Cerrado, through a more-than-huma-geopolitics. For this we make use of the Actor-Network-Theory (ANT) as a way to contemplate both human and non-human actants. In order to present a historical construction of the Brazilian Cerrado as a space of security and (in)security; seeking to understand how different actor-networks strive to (de)securitize it as a means to establish agribusiness in the region. Thus arriving at the understanding that the contention to (re)frame the Cerrado articulates traditional and capitalist production with a plethora of non-humans, therefore, the agency of collectives of humans and non-humans involves a semiology and practices that stabilize or destabilize this collective.